Relation of hypoxia inducible factor 1 alpha and 2 alpha in operable non-small cell lung cancer to angiogenic/molecular profile of tumours and survival. - Giatromanolaki, A; Koukourakis, M; Sivridis, E; Turley, H; Talks, K; Pezzella, F; Gatter, K; Harris, A (2001)
Hypoxia inducible factors HIF1alpha and HIF2alpha are important proteins involved in the regulation of the transcription of a variety of genes related to erythropoiesis, glycolysis and angiogenesis. Hypoxic stimulation results in rapid increase of the HIF1alpha and 2alpha protein levels, as a consequence of a redox-sensitive stabilization. The HIFalphas enter the nucleus, heterodimerize with the HIF1beta protein, and bind to DNA at the hypoxia response elements (HREs) of target genes. In this study we evaluated the immunohistochemical expression of these proteins in 108 tissue samples from non-small-cell lung cancer (NSCLC) and in normal lung tissues. Both proteins showed a mixed cytoplasmic/nuclear pattern of expression in cancer cells, tumoural vessels and tumour-infiltrating macrophages, as well as in areas of metaplasia, while normal lung components showed negative or very weak cytoplasmic staining. Positive HIF1alpha and HIF2alpha expression was noted in 68/108 (62%) and in 54/108 (50%) of cases respectively. Correlation analysis of HIF2alpha expression with HIF1alpha expression showed a significant association (P< 0.0001, r = 0.44). A strong association of the expression of both proteins with the angiogenic factors VEGF (P< 0.004), PD-ECGF (P< 0.003) and bFGF (P< 0.04) was noted. HIF1alpha correlated with the expression of bek-bFGF receptor expression (P = 0.01), while HIF2alpha was associated with intense VEGF/KDR-activated vascularization (P = 0.002). HIF2alpha protein was less frequently expressed in cases with a medium microvessel density (MVD); a high rate of expression was noted in cases with both low and high MVD (P = 0.006). Analysis of overall survival showed that HIF2alpha expression was related to poor outcome (P = 0.008), even in the group of patients with low MVD (P = 0.009). HIF1alpha expression was marginally associated with poor prognosis (P = 0.08). In multivariate analysis HIF2alpha expression was an independent prognostic indicator (P = 0.006, t-ratio 2.7). We conclude that HIF1alpha and HIF2alpha overexpression is a common event in NSCLC, which is related to the up-regulation of various angiogenic factors and with poor prognosis. Targeting the HIF pathway may prove of importance in the treatment of NSCLC.